Contemporary issues in educational policy and school outcomes - Hoy, Wayne K.; Miskel, Cecil G. (Research and theory in educational administration., 2006)
This book is the fifth in a series on research and theory dedicated to advancing our understanding of schools through empirical study and theoretical analysis. Scholars, both young and established, are invited to publish original analyses, but we especially encourage young scholars to contribute to this series. The current volume is similar to its predecessors in that it provides a mix of beginning and established scholars and a broad range of theoretical perspectives; in all 14 authors contributed to 9 separate but related analyses, which were selected for publication this year.